The Priority of Locomotion in Aristotle's Physics - Odzuck, Sebastian (Hypomnemata, 2014)
The book inquires into Aristotle's claim that of the four kinds of change that exist, locomotion is the most fundamental and important kind. In a first step, the author shows that the arguments for the thesis of locomotion's priority play a crucial role in the argument of Physics VIII and for the understanding of Aristotle's philosophy of nature in general. The main focus of the book lies on the thorough and careful reconstruction and analysis of the arguments Aristotle presents in Physics VIII.